2016
DOI: 10.5539/ies.v9n2p73
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting ICT Adoption among Distance Education Students based on the Technology Acceptance Model—A Case Study at a Distance Education University in Iran

Abstract: The incorporation of Information and Communication Technologies (ICT) into education systems is an active program and movement in education that illustrates modern education and enables an all-encompassing presence in the third millennium; however, prior to applying ICT, the factors affecting the adoption and use of these technologies should be carefully investigated. The present study was conducted to examine the factors affecting ICT adoption among distance education students based on the Technology Acceptan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 3 publications
0
6
0
2
Order By: Relevance
“…The response of acceptance or rejection then affects the individual's decision. While the perception of usefulness and ease of use directly affects individuals' attitudes (Dastjerdi, 2016), changes in attitude also determine the behavioral intention to use technology (Lee et al, 2007). In this sense, this study aims to evaluate the usability of VRP-C for robotics programming education from the perspective of pre-service CS teachers.…”
Section: Attitude Towardmentioning
confidence: 99%
“…The response of acceptance or rejection then affects the individual's decision. While the perception of usefulness and ease of use directly affects individuals' attitudes (Dastjerdi, 2016), changes in attitude also determine the behavioral intention to use technology (Lee et al, 2007). In this sense, this study aims to evaluate the usability of VRP-C for robotics programming education from the perspective of pre-service CS teachers.…”
Section: Attitude Towardmentioning
confidence: 99%
“…A thoughtful research on factors affecting technology integration comes from neighboring continent of Asia, Middle East country, Iran. Dastjerdi, (2016), an Iranian researcher explored other factors affecting technology integration in language teaching than educational agent; ICT usefulness among distance education students based on technology acceptance model in Iran. His research result showed perceived usefulness has a direct effect on the decision to use technologies, while the attitude toward technologies affected the decision to use technologies.…”
Section: Factors Affecting Technology Integration In English Languagementioning
confidence: 99%
“…performance will be improved in frame of the relevant topic after using the relevant technology; while perceived ease of use is referred to as the opinion that the individual can use the relevant technology by spending very little effort (Hsia, 2016). It is stated under the model that an individual's perceived ease of use and perceived usefulness in respect of a technology have an effect on determining the attitude of such individual towards using the relevant technology; that the individual's attitude towards the use of technology directly influences, while perceived ease of use and perceived usefulness indirectly influences, such individual's intention to use technology (Dastjerdi, 2016). Depending on the intention towards using the relevant technology, the individual will develop a behavior to use the technology (Davis, 1993).…”
mentioning
confidence: 99%
“…performansının artacağı inancı; algılanan kullanım kolaylığı ise, bireyin ilgili teknolojiyi çok az çaba harcayarak kullanabileceği inancı olarak açıklanmaktadır (Hsia, 2016). Modelde, bireyin ilgili teknolojiyi kullanmaya yönelik tutumunu belirlemede, o teknoloji ile ilgili bireydeki algılanan kullanım kolaylığı ve algılanan faydanın etkili olduğu; bireyin teknolojiyi kullanmaya yönelik niyetini belirlemede de bireyin teknolojiyi kullanmaya yönelik tutumunun doğrudan etkili olduğu, algılanan kullanım kolaylığı ve algılanan faydanın dolaylı olarak etkili olduğu belirtilmektedir (Dastjerdi, 2016). İlgili teknolojiyi kullanmaya yönelik niyetine bağlı olarak bireyde teknolojiyi kullanma davranışı gerçekleşmektedir (Davis, 1993).…”
unclassified